Body composition, anaerobic power, lower extremity strength in football players: Acute effect on different leagues - Hamza Küçük; Mehmet Söyler (Turkish Journal of Kinesiology)
The aim of the study was to compare differences in body composition, lower extremity strength, and anaerobic power characteristics among professional football players at different league levels. A total of seventy-one volunteer players aged between eighteen and thirty-five years (mean age: 23.14 ± 4.23 years) participated in the study, representing the Super League, 1st League, and 2nd League. The participants' body compositions were measured using the DXA (Hologic QDR Series, Delphi A model, Bedford, MA, USA) bioelectrical impedance analyzer, CounterMovement Jump (CMJ) strength with the ChronoJump Smartspeed Mat (INEFC, Barcelona), and Running Anaerobic Sprint Test (RAST) tests were conducted. ANOVA was used to compare multiple groups, and the Duncan multiple comparison tests were conducted in cases where differences were observed to determine which group the difference favored. The results revealed that Super League players statistically possessed more significant values in body composition compared to 1st and 2nd League players and demonstrated significantly higher values in terms of jump height, maximum force output, and anaerobic power compared to 1st and 2nd League players (p